Expression of Cytochrome P450 Pathway Genes CYP3A4 and CYP2D6 in the Liver and Pancreas of STZ-Induced Diabetic Rats: Cytochrome P450 Pathway Genes CYP3A4 and CYP2D6 in STZ-Induced Diabetic Rats - Iqbal, Neelam; Iqbal, Fizza; Aman, Sitwat; Ahmad, Asma; Faridi, Tallat Anwar; Obeagu, Emmanuel Ifeanyi (MARKHOR (The Journal of Zoology), 2026)
Diabetes mellitus disrupts metabolism and can alter hepatic drug-metabolizing enzymes, including CYP450 isoforms. Medicinal plants like Eucalyptus globulus and Psidium guajava exhibit antihyperglycemic effects, but their impact on CYP3A4 and CYP2D6 expression in diabetes is not well understood. Objectives: To evaluate the antihyperglycemic effects of Eucalyptus globulus and Psidium guajava extracts and to investigate the expression of CYP3A4 and CYP2D6 genes in the liver and pancreas of streptozotocin (STZ)-induced diabetic rats. Methods: This controlled experimental laboratory animal study was conducted on 36 male albino rats divided into six groups (n=6). Diabetes was induced using streptozotocin (STZ)–nicotinamide. Diabetic groups were treated with stem and leaf extracts of Eucalyptus globulus and Psidium guajava for 15 days. Blood glucose levels were monitored using a glucometer. Expression of CYP3A4 and CYP2D6 in liver and pancreatic tissues was analyzed by RT-PCR, and histopathological examination was performed. Results: STZ administration significantly elevated blood glucose levels compared to controls, confirming successful induction of diabetes. Treatment with plant extracts, particularly Eucalyptus globulus stem extract, significantly reduced hyperglycemia. In liver tissue, CYP3A4 expression was downregulated in diabetic rats, while CYP2D6 expression was upregulated. Plant treatment tended to restore expression levels toward normal. In pancreatic tissue, *Cyp3a1/2* and Cyp2d expression were not detected by semi-quantitative RT-PCR under the present experimental conditions. Conclusions: STZ-induced diabetes alters hepatic CYP450 gene expression, potentially affecting drug metabolism. Eucalyptus globulus, particularly the stem extract, demonstrated notable antihyperglycemic activity and partially normalized hepatic CYP expression.